Model Sebaran Lokasi Pedagang Kaki Lima dengan Simulasi Multi-Agent - Rafid Mahful; Ihsan Ihsan; Isfa Sastrawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2017)
The lack of the formal sector makes people look for other ways to survive, the informal sector is one way to reduce the possibility of social unrest in the community, for example the informal sector is a street vendor. The growth rate of street vendors in Makassar City is very rapid until November 2013, the number is around 14,000 people. The problem of the speed of street vendors in Makassar City is one of the factors causing the behavior of street vendors. This study aims to identify the characteristics of the location of trading and distribution patterns of street vendors, identify the factors influencing street vendors in choosing a location to trade and build a model of distribution of street vendor locations along the Losari Beach corridor. The analytical method used is descriptive analysis, frequency distribution, and multi-agent simulation. The results of this study indicate that the characteristics of the group of street vendors in Losari Beach are linear, spreading, and grouping patterns. Factors influencing the pattern of distribution are crowds, security, access, groups, kinship, rivalry, and retribution. From the results of the simulation, it can be seen that the types of street vendors who are in groups are types of drinks, banana epe, toys, meatballs, and boiled peanuts. Furthermore, linear street vendors are only bananas, while street vendors whose distribution patterns are spread are toys, sweet potato chips, meatballs, boiled peanuts, sausages, mixtures, accessories, clocks, and clothes.